Miranda's Final Frontier - the International Arena: A Critical Analysis of U.S. v. Bin Laden, and a Proposal for a New Miranda Exception Abroad - Godsey, Mark A. (2002)
In recent years, the FBI and other federal law agencies have greatly expanded their presence abroad, investigating everything from narcotics trade and internet fraud schemes to terrorism. This trend will undoubtedly continue in the aftermath of September 11th. A constitutional question that will be of increasing importance in this context is whether, or to what extent, U.S. law enforcement officials (hereinafter FBI ) must provide Miranda warnings to non-U.S. citizens interrogated abroad who will later be tried in the United States. The article first addresses whether future modifications to the Miranda doctrine are permissible after Dickerson. The article concludes that despite the warnings of some scholars that Dickerson has caused Miranda to become frozen in time, Dickerson should be read as creating a prophylactic Miranda rule that is both constitutionally-based and flexible at the same time. Thus, exceptions to the Miranda doctrine can be made, as in Quarles, in new contexts where its application is illogical or where the state's interests outweigh the civil liberties interests involved. The article then argues that the policies behind Miranda do not always support its application abroad in the same way that it is systematically applied in the domestic setting. Indeed, as demonstrated through a series of hypothetical scenarios, a strict application of Miranda abroad would not always further the civil liberties that the doctrine was designed to protect, and would simultaneously undermine U.S. law enforcement interests by freezing out the United States from participating in interrogations in many foreign countries. The article proffers that an FBI agent abroad should be required to advise a non-U.S. citizen suspect only of the rights that he enjoys in the country where the interrogation takes place, to the extent such rights can be reasonably determined by the FBI agent under the circumstances of the interrogation. In addition, if the FBI agent makes a mistake in interpreting the rights available to a given suspect under foreign law, and does not advise the suspect of a right which he in fact had, the exclusionary rule should not be employed as long as the agent misinterpreted the foreign law in good faith